2007
DOI: 10.1128/jvi.01434-06
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Two Nuclear Localization Signals of Influenza A Virus Nucleoprotein to Viral Replication

Abstract: The RNA genome of influenza A virus, which forms viral ribonucleoprotein complexes (vRNPs) with viral polymerase subunit proteins (PA, PB1, and PB2) and nucleoprotein (NP), is transcribed and replicated in the nucleus. NP, the major component of vRNPs, has at least two amino acid sequences that serve as nuclear localization signals (NLSs): an unconventional NLS (residues 3 to 13; NLS1) and a bipartite NLS (residues 198 to 216; NLS2). Although both NLSs are known to play a role in nuclear transport, their relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
222
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(243 citation statements)
references
References 32 publications
21
222
0
Order By: Relevance
“…Similar studies have now been reported for all eight segments (summarized in Fig. 4c), and in every case, the terminal coding regions, comprising sequences unique for each segment, have been found to promote more efficient packaging than the UTRs alone (Dos Santos Afonso et al, 2005;Fujii et al, 2003;Fujii et al, 2005;Gog et al, 2007;Liang et al, 2005Liang et al, , 2008Marsh et al, 2007;Muramoto et al, 2006;Ozawa et al, 2007Ozawa et al, , 2009Watanabe et al, 2003). The observation that virus formation is inefficient in the absence of the terminal regions of all eight vRNAs has also been corroborated and extended by examining the effects of removing other segments (de Wit et al, 2006;Fujii et al, 2009;Gao et al, 2008;Gao & Palese, 2009;Marsh et al, 2007).…”
Section: Genome Segmentation: a Mixed Blessingsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar studies have now been reported for all eight segments (summarized in Fig. 4c), and in every case, the terminal coding regions, comprising sequences unique for each segment, have been found to promote more efficient packaging than the UTRs alone (Dos Santos Afonso et al, 2005;Fujii et al, 2003;Fujii et al, 2005;Gog et al, 2007;Liang et al, 2005Liang et al, , 2008Marsh et al, 2007;Muramoto et al, 2006;Ozawa et al, 2007Ozawa et al, , 2009Watanabe et al, 2003). The observation that virus formation is inefficient in the absence of the terminal regions of all eight vRNAs has also been corroborated and extended by examining the effects of removing other segments (de Wit et al, 2006;Fujii et al, 2009;Gao et al, 2008;Gao & Palese, 2009;Marsh et al, 2007).…”
Section: Genome Segmentation: a Mixed Blessingsupporting
confidence: 73%
“…(c) Packaging of reporter genes. The shortest sequences shown to cause efficient packaging of reporter genes are indicated by green bars Fujii et al, 2005;Liang et al, 2005;Marsh et al, 2007;Ozawa et al, 2007Ozawa et al, , 2009). The region indicated for segment 7 promotes packaging relatively poorly, and may not contain the complete packaging signal (Muramoto et al, 2006;Ozawa et al, 2009).…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 99%
“…A previous study showed that soon after budding, the influenza A virus ribonucleoprotein (RNP) complexes inside the virions form a specific architecture: a central segment surrounded by the seven other vRNPs (2), which suggests that influenza viral RNA (vRNA) packaging is not a random process. Moreover, segment-specific RNA packaging sequences have been identified on each segment of the influenza A/WSN/33 virus (3)(4)(5)(6)(7)(8)(9)(10)(11). A common feature of these packaging signals is that both the 3Ј and 5Ј noncoding regions (NCRs), as well as coding sequences at the two ends of each open reading frame (ORF) are important [(3-11) and Fig.…”
Section: Nfluenza Viruses Are Classified As Members Of the Familymentioning
confidence: 99%
“…Surprisingly, except for the 12 conserved nucleotides at the 3Ј end and the 13 nucleotides at the 5Ј end of the vRNA, which are required for both polymerase recognition and binding (1), no other conserved motif has been identified in the remainder of the packaging sequences. In addition, the minimum lengths required for efficient packaging, either at the 3Ј or 5Ј ends of the vRNA, differ from one segment to another (3)(4)(5)(6)(7)(8)(9)(10)(11). Although much is known about the role of these packaging sequences in influenza RNA packaging, their mechanism has yet to be fully elucidated.…”
Section: Nfluenza Viruses Are Classified As Members Of the Familymentioning
confidence: 99%
“…Using reverse genetics, cispackaging signals of the human H1N1 WSN and PR8 strains were found to reside at both ends of each vRNA, including the UTRs, along with up to 80 bases of adjacent coding sequences (21)(22)(23)(24)(25)(26)(27)(28). In this study, we generated reassortant viruses in vitro from avian H5N2 and human H3N2 viruses to identify incompatibilities between the two parental viruses arising at the vRNA level.…”
mentioning
confidence: 99%